P53 Expression in Colorectal Carcinoma: The University of Malaya Medical Centre’s Experience - Goh, K.S.K.; Ong, T.A.; Peh, S.C.; Yuen, H.L.; Naicker, M. (Malaysian Medical Association, 2004)
Loss of P53 function is regarded as one of the critical steps in colorectal carcinogenesis. This study determines the P53 expression pattern of colorectal carcinoma in a cohort of 116 local patients. There was no significant relationship between overexpression of P53 with tumour stage (p=0.209, chi square test) and grade (p=0.877, chi square test). Survival analysis using Kaplan-Meier procedure did not show significant relationship between P53 positivity with overall recurrence-free and survival outcome (p=0.3322 and 0.921 respectively; log rank test). Long- term follow-up may give a better evaluation on the prognostic value of P53 overexpression in colorectal carcinoma.